KASHMIRI WOMEN AS THE AGENT OF CLIMAT CHANGE - Shabir Ahmad Dar; Dr. J. Muthukumar; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
In recent years, the increasing awareness of environmental concerns and its effect on public consciousness has become one of the most noticeable trends on a global level. Environmental degradation is a major threat to the life of society in the current days. The global community's unfulfilled promise of a society in which every woman enjoys complete gender equality, as well as the eradication of all legal, social, and economic obstacles to women empowerment, persists. Education disadvantages result into a lack of access to skills and opportunities in many areas of growth and development. Gender inequality is a basic human right regardless of where you live. Women comprise the largest proportion of the impoverished are the most vulnerable and disadvantaged group. This community depends more on natural resources, but has less access to them. In fact, they often face a significant burden for procuring food, water, and fuel. These areas are mostly threatened by climate change. In Kashmir women is consider as agent beyond these disasters. Hence an attempt has been made to emphasis the aura of Kashmir Valley and women as agent of change.